Dissolution of WO3 modified with IrOx overlayers during photoelectrochemical water splitting. Issue 1 (11th January 2023) - Jenewein, Ken J.; Knöppel, Julius; Hofer, André; Kormányos, Attila; Mayerhöfer, Britta; Speck, Florian D.; Bierling, Markus; Thiele, Simon; Bachmann, Julien; Cherevko, Serhiy
Abstract: WO3, an abundant transition metal semiconductor, is one of the most discussed materials to be used as a photoanode in photoelectrochemical water‐splitting devices. The photoelectrochemical properties, such as photoactivity and selectivity of WO3 in different electrolytes, are already well understood. However, the understanding of stability, one of the most important properties for utilization in a commercial device, is still in the early stages. In this work, a photoelectrochemical scanning flow cell coupled to an inductively coupled plasma mass spectrometer is applied to determine the influence of co‐catalyst overlayers on photoanode stability. Spray‐coated WO3 photoanodes are used as a model system. Iridium is applied to the electrodes by atomic layer deposition in controlled layer thickness, as determined by ellipsometry and x‐ray photoelectron spectroscopy. Photoactivity of the iridium‐modified WO3 photoanodes decreases with increasing iridium layer thickness. Partial blocking of the WO3 surface by iridium is proposed as the main cause of the decreased photoelectrochemical performance. On the other hand, the stability of WO3 is notably increased even in the presence of the thinnest investigated iridium overlayer. Based on our findings, we provide a set of strategies to synthesize nanocomposite photoelectrodes simultaneously possessing high photoelectrochemical activity and photostability. Abstract : Operando photodegradation is measured with a photoelectrochemical scanning flow cell connected to an inductively coupled plasma mass spectrometer for WO3 decorated with atomic layer‐deposited IrO x overlayers. The application of an overlayer drastically suppresses the tungsten dissolution during photoelectrochemical water splitting, but increasingly blocks the light path to the photoabsorber as the overlayer thickness increases, manifesting in lower photocurrents.